Consumption and identity at work - Du Gay, Paul (Sage Publications, 1996)
The realms of consumption have typically been seen to be distinct from those of work and production. This book examines how contemporary rhetorics and discourses of organizational change are breaking down such distinctions - with significant implications for the construction of subjectivities and identities at work. In particular, Paul du Gay shows how the capacities and predispositions required of consumers and those required of employees are increasingly difficult to distinguish. Both consumers and employees are represented as autonomous, responsible, calculating individuals. They are constituted as such in the language of consumer cultures and the all-pervasive discourses of enterprise whereby persons are required to be.